2017
DOI: 10.1016/j.carbon.2016.12.091
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of two-photon oxidized graphene

Abstract: Chemical composition of two-photon oxidized single-layer graphene is studied by micrometer X-ray photoelectron spectroscopy (XPS). Oxidized areas with a size of 2 x 2 µm 2 are patterned on graphene by tightly focused femtosecond pulsed irradiation under air atmosphere. The degree of oxidation is controlled by varying the irradiation time. The samples are characterized by four wave mixing (FWM) imaging and Raman spectroscopy/imaging. Micrometer-XPS is used to study local chemical composition of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…6 It was used in microcutting, 7,8 in ablation of graphene, [9][10][11][12][13] and in producing micro and nano-disks. 14 Direct laser writing was also applied for graphene oxide reduction, 15 for oxidation of graphene in controlled manner, 16,17 and patterning of p-n junction in graphene. 18 Recently, we demonstrated that optical forging, a direct laser writing method with tightly focused femtosecond laser beam under inert gas atmosphere, can be used for 3D shaping of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…6 It was used in microcutting, 7,8 in ablation of graphene, [9][10][11][12][13] and in producing micro and nano-disks. 14 Direct laser writing was also applied for graphene oxide reduction, 15 for oxidation of graphene in controlled manner, 16,17 and patterning of p-n junction in graphene. 18 Recently, we demonstrated that optical forging, a direct laser writing method with tightly focused femtosecond laser beam under inert gas atmosphere, can be used for 3D shaping of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many methods have already been used to modify graphene, including different strategies for tailoring its shape [5][6][7][8], defect control [9][10][11], chemical modification [12][13][14][15], besides many others. Recently, an all-optical method, namely, two-photon oxidation of graphene was demonstrated, which proved to have some advantages as compared to other oxidation methods, including direct writing of device features with sub-micrometer resolution, high speed and controlled level of oxidation [16][17][18][19]. Previous atomic force microscopy (AFM), Raman and X-ray photoelectron spectroscopy (XPS) studies showed a two-photon oxidation process starting with point-like functionalized sites evolving into oxidized islands and then forming a uniform graphene oxide (GO) material mainly composed of hydroxyl (OH) and epoxide (C−O−C) functional groups with a few per cent of carboxylic (COOH) groups [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, irradiation of the same sample with analogous patterns under air reveals characteristic signals of oxidized carbon (Supporting Information, Figure S3). 14,18,19 To further investigate the nature of the elevated plateaus we prepared a series of square patterns and compared them to square patterns made under air. In Figure 2a, two rows of squares patterned on graphene are presented.…”
mentioning
confidence: 99%